Portfolio Risk and Diversification: Bitcoin and Currencies Classics (Global Journal of Management and Business Research, 2025)
Industry 4 0 and digital transformation has accelerated the birth and emergence of virtual assets such as cryptocurrencies or cryptoassets Bitcoin is Virtual currency that has captured the major attention of finance theorists and practitioners This asset currency has achieved the highest market value to date The objective of this thesis is to verify this the behavior and relationship between bitcoin and several financial assets in the framework of an international diversification strategy of a composite portfolio Conventional and Crypto assets Bitcoin can thus be considered as a new asset class of diversification Faced with this observation between bitcoin and a selection of raw materials we have studied the relationship between bitcoin and a selection of currencies namely EUR GBP and JPY We refer to the value at risk VaR by three empirical methods and the conditional value at risk CVaR for a robustness target Data are daily from 29 10 2016 on 23 10 2020 We find that the inclusion of bitcoin in a diversified portfolio can significantly improve risk and rendement characteristics
Keywords: diversification; VaR; CVaR; bitcoin; EUR; GBP; JPY